EMG and 3D kinematics of the lower limb of male and female elite soccer players performing an unanticipated cutting task - Beaulieu, M.; Lamontagne, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study is to compare the timing of recruitment and the amplitude of the EMG signal, as well as the three-dimensional kinematics, of the lower limb of female and male elite soccer players performing an unanticipated cutting manoeuvre. Results showed that women performed the cutting task with significantly higher knee valgus angles at initial ground contact (IC) and higher peak knee valgus angles than men. Furthermore, onset of the semitendinosus and peak biceps femoris activity occurred significantly sooner for the female athletes than for the male athletes, which may increase strain on the ACL. Women also executed the task with greater RF and BF activity. This increased hamstring activity may be a compensatory mechanism to offset increased knee joint laxity in order to achieve functional joint stability.